2022
DOI: 10.52711/0974-360x.2022.00293
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Antioxidant and Anticholinesterase Activities of Extracts from the Leaves of Cassia moschata Kunth

Abstract: Alzheimer’s disease (AD) is a neurodegenerative disorder, which is the most common cause of dementia. This disease commonly occurs in elderly people. The increase in life expectancy means that that the number of people suffering from AD is expected to rise each year if there is no effective treatment found. The relation of cholinesterase and oxidative stress to Alzheimer’s disease has been reported. In our previous study, we have investigated the potency of the ethanolic extract of Cassia moschata leaves as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Amongst the plants tested, extracts from the leaves, stems, and flowers of C. timorensis showed significant inhibition against AChE [ 28 ]. We have investigated the cholinesterase inhibitory activities of various extracts from the leaves and stems of C. spectabilis that showed the potency of the leaves and stems extracts against both AChE and BChE enzymes [ 22 ]. Franca et al reported the AChE inhibitory potency of the methanolic extract of C. spectabilis flower using a TLC bioautography method, which however, cannot determine the activity quantitatively [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Amongst the plants tested, extracts from the leaves, stems, and flowers of C. timorensis showed significant inhibition against AChE [ 28 ]. We have investigated the cholinesterase inhibitory activities of various extracts from the leaves and stems of C. spectabilis that showed the potency of the leaves and stems extracts against both AChE and BChE enzymes [ 22 ]. Franca et al reported the AChE inhibitory potency of the methanolic extract of C. spectabilis flower using a TLC bioautography method, which however, cannot determine the activity quantitatively [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Silva et al synthesized 12 analogous from (−)-cassine and (−)-spectaline, and four of the semisynthetic compounds significantly inhibited BChE in the in vitro assay [ 38 ]. Our previous study showed that the ethanolic extract of C. spectabilis leaves contains piperidine alkaloids and displays significant cholinesterase inhibitory activities [ 21 , 22 ]. Based on the various reports on the potency of piperidine alkaloids as cholinesterase inhibitors [ 34 38 ], it can be suggested that the cholinesterase inhibitory activities of the ethanolic and water extracts of C. spectabilis flowers in this study possibly due to the presence of the piperidine alkaloids detected in the samples.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It protects against dopaminergic neuronal degeneration in the substantia nigra and striatum in MPTP-induced PD in rat models. The supplementation of C. obtusifolia attenuates cellular damage, depolarization of the mitochondrial membrane, and diminished ROS generation (Rizqiyah et al, 2022).…”
Section: Cassia Obtusifoliamentioning
confidence: 99%